Adolescent Reproductive Health Issues and Sexual Behaviors in Coastal Communities: A Case of Biriwa, Ghana - Afua Kumi-Takyiwaa (Department of Social Development and Welfare, Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2022)
Abstract Adolescence is a vital stage of human development because it is characterized by physical, mental, emotional, and psychological changes and sexual experimentation as an individual transitions from childhood to adulthood. This study investigated adolescent reproductive health issues and sexual behaviors in Biriwa, Ghana. The study draws on the health belief model and social learning theory components to analyze the motivations and responses toward reproductive health issues. The study employed a descriptive survey design, and a questionnaire was used to gather data from 200 adolescents. The study discovered the prevalence of unhealthy premarital sexual intercourse and consequent abortion of pregnancies. Peer pressure and lack of financial support from parents or guardians were the main factors that motivated adolescents to engage in unhealthy premarital sex. Therefore, it is recommended that the health center provide regular reproductive health education for adolescents in the community. Keywords: Adolescent, Sexual Behaviour, Sex, Reproductive Health Abstrak Masa remaja merupakan tahap vital perkembangan manusia karena ditandai dengan perubahan fisik, mental, emosional, dan psikologis serta eksperimentasi seksual sebagai transisi individu dari masa kanak-kanak menuju dewasa. Penelitian ini menyelidiki masalah kesehatan reproduksi remaja dan perilaku seksual di Biriwa, Ghana. Studi ini mengacu pada komponen model keyakinan kesehatan dan teori pembelajaran sosial untuk menganalisis motivasi dan tanggapan terhadap masalah kesehatan reproduksi. Penelitian ini menggunakan desain survei deskriptif, dan kuesioner digunakan untuk mengumpulkan data dari 200 remaja. Studi ini menemukan prevalensi hubungan seksual pranikah yang tidak sehat dan aborsi kehamilan. Tekanan teman sebaya dan kurangnya dukungan finansial dari orang tua atau wali menjadi faktor utama yang memotivasi remaja untuk melakukan hubungan seks pranikah yang tidak sehat. Oleh karena itu, disarankan agar Puskesmas memberikan pendidikan kesehatan reproduksi secara berkala kepada remaja di masyarakat. Kata Kunci: Remaja, Perilaku Seksual, Jenis Kelamin, Kesehatan Reproduksi